RELIGIOUS FESTIVALS - Chackalackal, Saju (Journal of Dharma, 2003)
Along with millions of people coming from different parts of Karnataka in India, I participated in the zenith-celebration of the nine-days long Dussehra in Mysore this year. It was an enriching experience as this celebration brought together factual history and mythical history in such a vivid and colourful celebration of the festival of Dussehra. What was more striking in this emotional participation of so many people, without the distinction of caste, colour, and even creed (as many religious festivals turn out to be more and more social, and, hence, less sectarian in participation), is the fact that it creates, induces, maintains and sustains a community consciousness, a consciousness shared by all that they do form one integral community, and, thus, opening up a common platform to eliminate all divergences, positively fostering unity at all levels.